RNA Sequencing Analysis of Intracranial Aneurysm Walls Reveals Involvement of Lysosomes and Immunoglobulins in Rupture. Issue 5 (May 2016) - Kleinloog, Rachel; Verweij, Bon H.; van der Vlies, Pieter; Deelen, Patrick; Swertz, Morris A.; de Muynck, Louis; Van Damme, Philip; Giuliani, Fabrizio; Regli, Luca; van der Zwan, Albert; Berkelbach van der Sprenkel, Jan W.; Han, K. Sen; et al.
Abstract : Background and Purpose—: Analyzing genes involved in development and rupture of intracranial aneurysms can enhance knowledge about the pathogenesis of aneurysms, and identify new treatment strategies. We compared gene expression between ruptured and unruptured aneurysms and control intracranial arteries. Methods—: We determined expression levels with RNA sequencing. Applying a multivariate negative binomial model, we identified genes that were differentially expressed between 44 aneurysms and 16 control arteries, and between 22 ruptured and 21 unruptured aneurysms. The differential expression of 8 relevant and highly significant genes was validated using digital polymerase chain reaction. Pathway analysis was used to identify enriched pathways. We also analyzed genes with an extreme pattern of differential expression: only expressed in 1 condition without any expression in the other. Results—: We found 229 differentially expressed genes in aneurysms versus controls and 1489 in ruptured versus unruptured aneurysms. The differential expression of all 8 genes selected for digital polymerase chain reaction validation was confirmed. Extracellular matrix pathways were enriched in aneurysms versus controls, whereas pathways involved in immune response and the lysosome pathway were enriched in ruptured versus unruptured aneurysms. Immunoglobulin genes were expressed in aneurysms, but showed no expression in controls. Conclusions—: For rupture of intracranial aneurysms, we identified the lysosome pathway as a new pathway and found further evidence for the role of the immune response. Our results also point toward a role for immunoglobulins in the pathogenesis of aneurysms. Immune-modifying drugs are, therefore, interesting candidate treatment strategies in the prevention of aneurysm development and rupture. Abstract : Supplemental Digital Content is available in the text.